1999
DOI: 10.1074/jbc.274.9.5835
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Signaling of Monocyte Inflammatory Cytokine Synthesis through an ERK1/2-dependent Pathway

Abstract: Ligation of CD40 on monocytes through its interaction with CD40 ligand (CD154) present on activated T helper cells, results in activation of monocyte inflammatory cytokine synthesis and rescue of monocytes from apoptosis induced through serum deprivation. Both of these consequences of CD40 stimulation have been shown to be dependent on the induction of protein tyrosine kinase activity. CD40-mediated activation of protein tyrosine kinase activity and subsequent inflammatory cytokine production are abrogated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
68
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 81 publications
5
68
1
Order By: Relevance
“…Whether or not stimulation of CD40 is involved in adipocyte differentiation or apoptosis deserves to be studied. Earlier studies showed that CD40 signalling results in the activation of the MAPK/ NF-κB pathways in monocytes/macrophages [33][34][35], thereby stimulating CD40-mediated induction of inflammatory cytokine synthesis. We found that in human adipocytes rCD40L treatment activated MAPKs and induced IκB protein degradation, which is known to activate and promote nuclear translocation of NF-κB, suggesting that increases in sCD40L or T-lymphocyte-expressing CD40L may play a role in the elevated activities of these factors in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not stimulation of CD40 is involved in adipocyte differentiation or apoptosis deserves to be studied. Earlier studies showed that CD40 signalling results in the activation of the MAPK/ NF-κB pathways in monocytes/macrophages [33][34][35], thereby stimulating CD40-mediated induction of inflammatory cytokine synthesis. We found that in human adipocytes rCD40L treatment activated MAPKs and induced IκB protein degradation, which is known to activate and promote nuclear translocation of NF-κB, suggesting that increases in sCD40L or T-lymphocyte-expressing CD40L may play a role in the elevated activities of these factors in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, involvement of Ras and Raf, the upstream regulators of ERK, in the regulation of TNF␣ production has been reported (26). Several investigators demonstrated that PD98059, an inhibitor of MEK, suppressed TNF␣ production in LPS-stimulated or CD154-stimulated monocytes (36)(37)(38)(39). Conversely, it has been reported that p38 is involved not only in the translation, but also in the stabilization of TNF␣ mRNA (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 also suppresses cyclooxgenase-2 expression by downregulation of p38 MAPK and ERK2 (31). Moreover, several reports have shown that IL-10 inhibits ERK1/2 activity and that this is important, for example, for the downregulation of polymorphonuclear neutrophil functions and CD40-mediated induction of IL-1␤ and TNF-␣ synthesis by monocytes (6,33,39).…”
Section: Discussionmentioning
confidence: 99%
“…In polymorphonuclear neutrophils, IL-10 exerts its anti-inflammatory properties by downregulating functions such as NADPH oxidase activation and reactive oxygen species production (6). Many of the anti-inflammatory actions of IL-10 are associated with inhibition of ERK1/2 activity or the MEK/ERK pathway (5,38,39).…”
mentioning
confidence: 99%
See 1 more Smart Citation